ANALYSIS STUDY OF INCLUSIVE ISLAMIC EDUCATION MODEL IN CREATING CHILD-FRIENDLY SCHOOLS SPECIAL NEEDS - Suprapno, Suprapno (Journal of Higher Education and Academic Advancement, 2024)
Objective: This study aims to explore the implementation of inclusive Islamic education for children with special needs, focusing on the challenges, opportunities, and its impact on their academic and social development. Method: The research employs a library research method, analyzing relevant scientific journal articles, books, and research reports. Results: The study finds that the application of inclusive Islamic education principles, such as creating supportive learning environments, fostering justice and compassion, and offering flexible curricula, helps children with special needs feel accepted. However, challenges such as limited resources, inadequate teacher training, and social stigma hinder full implementation. Opportunities exist through collaboration with non-profit organizations, teacher development, and public awareness initiatives, which can facilitate the transformation of schools into more inclusive spaces. The impact of this model is evident in the academic and social growth of children, who show improvements in learning achievements and social skills, including communication and cooperation. Novelty: This study contributes to understanding the integration of Islamic values in inclusive education models and highlights actionable opportunities for improving educational practices for children with special needs in Islamic schools. .